Model Pembelajaran Passing Bola Voli dengan Permainan pada Siswa Sekolah Menengah Pertama - Sukarno, Anova Putri Cucu; Samsudin, Samsudin; Sujarwo, Sujarwo (Jurnal Pendidikan Jasmani dan Adaptif (JPJA), 2024)
The purpose of this research is to produce a product of learning model of lower passing, upper passing and combination of passing with games that can be applied in the process of learning physical education in junior high school.  The results obtained from student questionnaires on a small scale are 85.26% for the level of convenience and 86.94% for the level of attractiveness, the results obtained from large-scale student questionnaires are 88.21% for the level of convenience and 84.98% for the level of attractiveness, the results obtained on the 7E class experimental scale are 77.72% for the level of convenience and 81.40% for the level of attractiveness of the volleyball passing learning model that the researchers made.